2013
DOI: 10.1111/2049-632x.12081
|View full text |Cite
|
Sign up to set email alerts
|

Role of theListeria monocytogenes2-Cys peroxiredoxin homologue in protection against oxidative and nitrosative stress and in virulence

Abstract: Peroxiredoxins contribute to protection of some bacteria against reactive oxygen intermediates (ROIs) and reactive nitrogen intermediates (RNIs). Listeria monocytogenes, a facultative intracellular bacterial pathogen, interacts with ROIs and RNIs during infection. In this study, we investigated the involvement of the 2-Cys peroxiredoxin (Prx) homologue in L. monocytogenes in the protection against ROIs and RNIs and in virulence through the construction of an in-frame prx deletion mutant. The Δprx mutant had in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
4
18
1
Order By: Relevance
“…Our comparison of H 2 O 2 and CHP confirms previous reports showing that H 2 O 2 is a more effective listericidal agent [27,30]. The presence of molecular oxygen, growth phase and serovar may all affect the response to oxidative conditions [26,31].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our comparison of H 2 O 2 and CHP confirms previous reports showing that H 2 O 2 is a more effective listericidal agent [27,30]. The presence of molecular oxygen, growth phase and serovar may all affect the response to oxidative conditions [26,31].…”
Section: Discussionsupporting
confidence: 88%
“…In food processing environments (FPE), various stressful conditions can influence L. monocytogenes growth and survival, especially refrigeration temperatures, osmotic, acid and oxidative stresses [24,25]. L. monocytogenes is also exposed to stressful conditions in hosts and some are common to FPE stresses: gastric acids provide acid and both invasion of phagolysosomes or macrophages and antibiotic treatments can cause oxidative stress [26,27]. L. monocytogenes is able to increase its tolerance to stressful conditions over time following repeated exposure to sub-lethal doses.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, there have been only a few studies on these nonclassical Ahp proteins (22,(27)(28)(29)(41)(42)(43). Although they are obviously homologs of E. coli and B. subtilis AhpC, the nonclassical Ahp proteins are a distinct class of proteins with significant sequence differences and, therefore, possibly functional differences from the classical Ahp proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Dons et al showed that 2-Cys peroxiredoxin (Prx) homologue (Lmo1604) showed protection against oxidative and nitrosative stress in vitro and in vivo. Lmo1604 also plays a role during infection to the host and protection against stress [20]. During host-pathogen interactions, oxidative stress genes were elevated indicating that these genes actively participate in this mechanism and are important for virulence [21].…”
Section: 1mentioning
confidence: 99%